Cancer cachexia: global awareness and guideline implementation on the web. Issue 2 (16th January 2013) - Mauri, Davide; Tsiara, Anna; Valachis, Antonis; Kalopita, Konstantina; Tsali, Lampriani; Tolis, Panagiotis; Polyzos, Nikolaos P
Abstract : Background: Cancer cachexia is a common associate of cancer and has a negative impact on patients' survival. Nonetheless, cancer cachexia assessment and management are frequently less than satisfactory in daily practice. Aim: To scrutinise global cancer cachexia awareness and relative web guideline implementation among oncology societies. Methods: Systematical identification of scientific and policymaker oncology societies and their guideline implementation on cancer cachexia. Assessment of the general level of awareness on cancer cachexia and evaluation of intercontinental and national variations on guideline implementation. Results: 144 000 web pages were scrutinised, and 275 oncology societies identified covering a large array of oncology setting (educational/clinical/research/policymaker); 71 were international (African, American, Asian, European, Oceania and Intercontinental), 110 belonged to the top 10 countries with the highest development index and 94 pertained to 10 countries with a long lasting tradition in medical oncology (not included in the top 10 high developed countries). Overall, only 10/275 web sites provided guidelines; six of them (2.2%) provided guidelines for physicians and four (0.7%) for patients. Half of the guidelines (4/10) were outdated. All guidelines for physicians reported references, while only one of the recommendations for patients reported references to support its sentences. Conclusions: Cancer cachexia global awareness appears extremely low; guideline implementation on the web was inconsistent for any category analysed (nation vs continent vs international vs society type vs physician vs patient oriented) and for updating.